Transboundary maritime cooperation: the case of the Eastern Caribbean Region - Mahadeo, Sarah; Del Savio, Linda (Frontiers in Marine Science, 2023)
Transboundary cooperation is a priority for the Organisation of Eastern Caribbean States (OECS). For over thirty years since its formation, it has pursued policies of integration and cooperation among its members with the aim of promoting development and reducing social and economic inequalities across the region. Within the last decade, the islands have embarked on ambitious plans for a sustainable Blue Economy, centred on developing the potential of their vast maritime zones. Achieving this requires cooperation across maritime borders for the management of shared natural resources and transnational human activities, as well as for addressing transboundary challenges facing the region such as climate change, marine pollution and Sargassum influxes. Through a literature review and documentary analysis this article provides a first stocktaking of transboundary maritime cooperation in the region through a mapping of regional level policy promoting cooperation and projects among OECS members over the last decade. The analysis reveals great diversity among participating countries, thematic priorities and actors operating across multiple governance levels. The article concludes with a discussion on the drivers for cooperation among OECS members, highlighting transboundary maritime cooperation as a natural and logical approach for capitalising on opportunities and addressing challenges in a capacity constrained region.